PHYSICO - CHEMICAL AND BIOLOGICAL WATER QUALITY OF KARACHI COASTAL WATER - Mashiatullah, A.; Qureshi, R. M.; Javed, T.; Ahmad, N.; Khalid, F. (The Nucleus, 2020)
Physiochemical and biological techniques have been applied to investigate Karachi Coastal water pollution due to Layari and Malir rivers, which mainly carry Karachi Metropolitan domestic and industrial wastewater. In Manora channel, which receives domestic sewage through Layari river, pH and electrical conductivity (E.C.) of seawater were less in low tide conditions as compared to high tide condition, and except for Manora Lighthouse all sampling stations exhibit E.C. below normal values of seawater, indicating fair proportion of Layari river water mixing in seawater. Coliform contamination ranged from 156 – 542 per 100 ml ( high tide) and 132- 974 per 100 ml (low tide) with increased levels observed in sampling sites close to Layari river outfall zone. Along Southeast coast, a decrease in EC was recorded at Ghizri area and Ibrahim Haideri fish harbour in low tide which indicated Malir river water input. Coliform bacterial counts at these locations were also above WHO guidelines for seawater bathing. pH and electrical conductivity values of Northwest coastal water indicated that this coast is marginally polluted. The study revealed that Karachi Metropolitan domestic sewage and industrial effluents are main source of coastal water pollution.